Pemanfaatan Teknologi IPUSNAS untuk Memperkuat Literasi Digital di Masyarakat Desa Rancabungur - Sugama, Alviansyah; Johandri, Johandri; Rahman, Rino; Karimah, Syahadah Albaqiyatul (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
This research proposes efforts to enhance digital literacy in the rural community of Rancabungur Village through the utilization of IPUSNAS technology. Digital literacy is key in addressing global digitalization challenges, and rural areas should not be left behind. Through this approach, we investigate how IPUSNAS can be used as a tool to improve digital understanding and skills within the village community. The research involves surveys, training, and the implementation of IPUSNAS to assist the people of Rancabungur Village in coping with the digital age. The results indicate a significant improvement in the digital literacy of the community, bringing substantial benefits to sustainable development in the village.